Hydraulic damage characteristics of cracks adjacent to sleepers of concrete slab. (1st February 2021) - Hu, Meng; Yang, Rongshan
Highlights: A formula of the hydrodynamic pressure in cracks adjacent to sleepers was derived. A laboratory experiment of the hydrodynamic pressure has been conducted. Temporal and spatial characteristics of hydrodynamic pressure were studied. Fatigue hydraulic damage of cracks adjacent to sleepers was studied. Abstract: In order to investigate the hydraulic damage characteristics of cracks adjacent to twinblock sleepers and estimate its fatigue life, an analytical expression of the hydrodynamic pressure in cracks under the external load was derived, and a hydraulic fracturing model of twinblock sleeper has been established based on the vehicle-track coupling dynamics theory and fracture mechanics theory. In addition, a laboratory test was conducted to verify the hydrodynamic pressure expression. It was observed that the computed results are in good consistent with the experimental results. The value of the hydrodynamic pressure in the crack peaks when the wheelset is close to the cracking area, while the hydrodynamic pressure is zero when the wheelset or the bogie reaches the damaged area. Numerous factors affect the hydrodynamic pressure and the effective stress intensity factor, including the train speed, crack opening, and crack length. In comparison, the hydrodynamic pressure and the effective stress intensity is more sensitive to the crack opening. The initial crack length is the main factor affecting the fatigue life of the crack. If the initial crack length is long enough, the critical fracture length can be easily reached under the coupling effect of the train load and water.